O livro e o axé, o erê com ganga zumba: representações afro-brasileiras na produção editorial didática voltada à lei 10.639/2003 e apropriação dos professores - Patrocinio, Fernanda de Araújo (2016)
This research is about schoolbooks, the ones published after the law 10.639/2003 and that brings the Afro-Brazilian right as main theme, and the teacher s adjustment, to promote the Education for all considering the Human Rights. The main idea of this study is around the question: what are the Afro-Brazilian representations from nominations, adjectives, actions, tensions, conflicts and negotiations that are present on the book s narratives? This study is relevant in recognition of the status of right of the Afro-Brazilians and the public politics need s for that. Therefore, considering this, one of the themes related here is the prejudice and the racism. The focus is on the dialogue about democratic and inclusive actions related to Education and the Afro-Brazilian culture as a part of the Brazilian culture, based on the symbolic level of the editorial and mediatic representations. The methodology is based on the bibliographic search and the uses of the narratology to analyses the selected products for the corpus. In addition to this, there are interviews with teachers to let us know more about their adjustment with the law 10.639/2003 and its schoolbooks. These teachers are from São Paulo and Rio Grande do Sul.